Optimalisasi Pelayanan Perizinan Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Melalui Mal Pelayanan Publik Kota Tangerang Selatan - Sabrina Putri Sujatmiko; Nanan Sujana; Refly Badar (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research contains that public services still have many deficiencies and important problems that still occur in the process of providing public services. In this case, there are still a few agencies that are required to provide services with standard operating procedures, and there is clarity. There are still several responsible agencies and service providers that do not yet have SOPs (Standard Operating Procedures) in the form of clear procedures for providing services. So that service delivery is still not effective and efficient and can be detrimental to the time of people who are accessing services. This study uses the theory of Parasuraman, Zheitaml and Berry (2013), suggesting that there are five principles that must be considered for the implementation of public services, which include: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This study used a descriptive qualitative method which is a qualitative method that refers to data collection in the form of observation, interviews, documentation and researchers acting as observers. So that overall the optimization of DPMPTSP licensing services in an effort to improve public services has been carried out quite well but needs to be optimized.